Effect of the two drying approaches on the volatile profiles of button mushroom (Agaricus bisporus) by headspace GC–MS and electronic nose. (October 2016) - Pei, Fei; Yang, Wenjian; Ma, Ning; Fang, Yong; Zhao, Liyan; An, Xinxin; Xin, Zhihong; Hu, Qiuhui
Abstract: Button mushroom slices were dehydrated using freeze drying (FD) or combined with microwave vacuum drying (FMVD), and the changes in volatile composition were investigated and compared by using headspace GC–MS and electronic nose (E-nose). The results showed that the content of C8 compounds decreased during FD/FMVD process, while more alkanes and heterocyclic compounds were generated in the latter drying periods. The content of original thermal volatile compounds in FMVD products were significantly lower compared to FD, and the same trent was observed on alkanes and heterocyclic compounds. Moreover, the volatile compounds of FMVD products were more similar with fresh ones according to cluster analysis, and the critical point of change of volatile compounds might be at the end of sublimation period. In addition, E-nose could clearly discriminate button mushroom samples subject to different drying periods, the result obtained by E-nose showed good identity compared with GC–MS. Highlights: Freeze drying (FD) or combined with microwave vacuum drying (FMVD) was investigated. The volatile profiles of button mushroom during two drying processes were examined. FMVD products contented lower alkanes, heterocyclic and original volatile compounds. The volatile compounds of FMVD products were more similar with fresh mushroom. E-nose could clearly discriminate samples subject to different drying periods.